A review of the worldwide distribution of Marenzelleria viridis, with new records for M. viridis, M. neglecta and Marenzelleria sp. (Annelida: Spionidae) - Radashevsky, Vasily I.; Pankova, Victoria V.; Malyar, Vasily V.; Cerca, José; Struck, Torsten H. (Zootaxa, 2021)
Marenzelleria Mesnil, 1896 is a small group of spionid polychaetes comprising five valid species, all of which appear similar to each other. The identification of worms based on morphological features is often confusing, and thus molecular data have been suggested as providing crucial additional diagnostic characters. Here we summarize and map available records of M. viridis (Verrill, 1873) worldwide, and, based on the analysis of fragment sequences of COI, 16S, 18S, 28S and Histone 3, report this species for the first time from Norway. We also summarize and map the records of Marenzelleria from North America, distinguishing those based on morphology and molecular data. We report new records for Marenzelleria sp. from Baffin Is., Nunavut, Canada, and for M. neglecta Sikorski & Bick, 2004 from Washington, USA.